CRITICAL DISCOURSE ANALYSIS ON TWITTER WITH 2019GantiPresiden HASHTAG: ANALISIS WACANA KRITIS DALAM KICAUAN (TWEET) TWITTER BERTAGAR 2019GantiPresiden - Hersila Astari Pitaloka (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
This study aims to describe the strategy and meaning of the tweet on Twitter with the hashtag 2019GantiPresiden. This type of research is descriptive with a qualitative approach. Data source in the form of uploaded Twitter account with 2019GantiPresiden hashtags in the form of verbal writing. Data collection techniques using the stages of reading and note-taking. Data analysis techniques were also carried out in-depth using critical discourse analysis methods adapted from the Fairclough (1995) model, namely (1) description, (2) interpretation, and (3) explanation. The results of the study found three speech strategies that were used by the 2019 non-presidential twitchy uploaders, namely (1) distorting facts, (2) analogies, and (3) satire (satire). This strategy forms a societal ideology, namely (1) the ideology of rejection of government policies, (2) the ideology of defending people's rights, and (3) the ideology of justifying their group.